Culture and psychology - David Matsumoto; Juang, Linda (New Delhi Cengage Learning India Pvt. Ltd., 2017)
An introduction to culture and psychology; Cross cultural research methods; Enculturation; Cultural and developmental processes; Culture self and identity; Culture and personality; Culture and gender; Culture and cognition; Culture and emotion; Culture language and communication; Culture and health; Cultural and psychological disorders; Culture and treatment for psychological disorders; Culture and social behavior; Culture and organization.
Keywords: Racial and Ethnic Psychology